2015
DOI: 10.1128/ec.00104-15
|View full text |Cite
|
Sign up to set email alerts
|

N-Terminal Presequence-Independent Import of Phosphofructokinase into Hydrogenosomes of Trichomonas vaginalis

Abstract: bMitochondrial evolution entailed the origin of protein import machinery that allows nuclear-encoded proteins to be targeted to the organelle, as well as the origin of cleavable N-terminal targeting sequences (NTS) that allow efficient sorting and import of matrix proteins. In hydrogenosomes and mitosomes, reduced forms of mitochondria with reduced proteomes, NTS-independent targeting of matrix proteins is known. Here, we studied the cellular localization of two glycolytic enzymes in the anaerobic pathogen Tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 56 publications
0
24
1
Order By: Relevance
“…Moreover, recombinant PDI‐BirA‐V5 was expressed under the control of a weak promoter to avoid any possible mistargeting due to the strong expression of recombinant proteins (Rada et al. ). In transfected cells, PDI‐BirA‐V5 appeared in the typical ER ring around the nucleus and tubulovesicular structures (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, recombinant PDI‐BirA‐V5 was expressed under the control of a weak promoter to avoid any possible mistargeting due to the strong expression of recombinant proteins (Rada et al. ). In transfected cells, PDI‐BirA‐V5 appeared in the typical ER ring around the nucleus and tubulovesicular structures (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we transformed the cell line expressing BirA-V5 in the cytosol with vectors that allowed the expression of the complete aor b-SCS with a C-terminal ACP and HA tag. Immunofluorescence microscopy of double-transfected trichomonads revealed that biotinylated aand b-SCS-ACP-HA localized exclusively to spherical vesicles exhibiting a distribution, number, and shape corresponding to hydrogenosomes (Dolezal et al 2005;Hrd y et al 2004;Rada et al 2011Rada et al , 2015Wexler-Cohen et al 2014). No labeling of structures associated with the secretory pathway or plasma membrane was observed.…”
Section: A-and B-scs Are Targeted Exclusively To the Hydrogenosomesmentioning
confidence: 92%
See 1 more Smart Citation
“…The cells were prepared for immunofluorescence microscopy as described elsewhere (Rada et al ., ). The recombinant proteins were detected in trichomonads using a mouse monoclonal anti‐HA antibody or a rabbit monoclonal anti‐V5 antibody (Abcam).…”
Section: Methodsmentioning
confidence: 97%
“…The cells were fixed on high‐precision cover glasses (Carl Zeiss, Germany) for super‐resolution microscopy and prepared for immunofluorescence microscopy as described elsewhere (Rada et al ., ). The recombinant proteins were detected in trichomonads using a mouse monoclonal anti‐HA antibody (Exbio, Czech Republic).…”
Section: Methodsmentioning
confidence: 97%